Metaphor in the Context of Baltic Music: the Idea of Eternal Return - Jūratė Landsbergytė-Becher (Pitannâ Lìteraturoznavstva, 2020)
Metaphor is the essential form for building momentum in the phenomenon of Baltic music. It created a new silent style of defensiveness and transcendentality, which eventually could help to change the self-awareness of the nation. The purpose of this article is to research the linguistic power of a metaphor, its transfer into the music and how it helped to uncover disinformation in the period of Soviet ideological domination. The comparative methodology is used to examine metaphors in the areas of music, literature, political science, and aesthetics of art philosophy. This article is structured to show the motion of metaphor in particular turns of time. Metaphor is a powerful instrument to raise the dimensions of the archetypes of national identity and statehood rights. Its usage could be compared with religion, nature, sacrality of space and history, and it is necessary for the change in the knowledge about the nation’s development. Metaphor is the renewed road to comprehend the importance of statehood existence and what happened in Baltic states during the times of crucial changes. It could be said that the metaphor helped to regain independence without the army and spreads its influence similarly at the present day, penetrating the new media streams connecting the matters of statehood. The article findings summarise the origins of the power of the nation based on the phenomenon of the resurrection of archetypes (under the theory of C. G. Jung), which were rediscovered by using principles of psychology.